Techniques and principles in language teaching. - Larsen-Freeman, Diane, 1946-; Anderson, Marti, ....- (Oxford : University Press, 2011)
Techniques and Principles in Language Teaching has influenced the way thousands of teachers have taught English. This classic guide to developing the way you teach has been an essential resource to new and experienced teachers worldwide, and is now in its third edition. Each chapter focuses on a different teaching approach, describing it being used in the classroom, analyzing what happened, and helping you think how you could apply it to your own teaching. New features of the third edition include: a new discussion on the political dimensions of language teaching, a new digital technology chapter, and extended coverage of content-based and task-based approaches. On this site you will find additional resources, including author videos in which Diane Larsen-Freeman and Marti Anderson talk about the background to the book and new innovations in language teaching which are discussed in the third edition.
Keywords: Engels; Vreemde-talenonderwijs.